Analyzing the Impact of Social Stigma on Children with Intellectual Disabilities: Causes, Consequences, and Strategies for Reduction - Putri Mayang Nugroho; Khairun Nisa; Nayla Candra Kirana; Farhah Amalia Syahrani; Citra Ashri Maulidina; Mohammad Arif Taboer (International Disability Innovation Journal, 2025)
Social stigma against children with intellectual disabilities is a serious issue that is still often encountered in various aspects of life, from education to social involvement. This stigma manifests in the form of social avoidance, negative labeling, discrimination, and violence, which have a significant impact on the growth and well-being of the child and their family. This article aims to analyze the various forms, causes, and consequences of social stigma faced by children with intellectual disabilities and to explore ways to reduce that stigma. This analysis was conducted using a literature review method that includes context, methodology, and theory. Data were obtained from scientific articles published between 2020 and 2025, accessed via Google Scholar; a total of 10 articles were analyzed. The findings of the analysis indicate that stigma remains a significant barrier for children with intellectual disabilities in obtaining their rights fairly, especially in the fields of education and social welfare. Nevertheless, approaches such as family and community support and the implementation of inclusive education have proven effective in reducing that stigma. Through collaborative efforts from various parties, an inclusive environment free from discrimination for children with intellectual disabilities can be realized.